CCAFS: A Proposed New Agenda for Research and Development - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Presentation by CGIAR Climate Program Director Bruce Campbell. Mr. Campbell talks about a new agenda for research and development. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya